Web site cookbook - Addison, Doug (Doug R.) (Web programming., 2006)
The total number of web pages today has been estimated at over 3 billion, spanning millions of individual websites. Not surprisingly, there is tremendous pressure on web developers and designers to remain current with the latest technologies. The Web Site Cookbook from O'Reilly covers all the essential skills that you need to create engaging, visitor-friendly websites. It helps you with the practical issues surrounding their inception, design, and maintenance. With recipes that teach both routine and advanced setup tasks, the book includes clear and professional instruction on a host of topics, including: registering domains ensuring that hostnames work managing the directory maintaining and troubleshooting a website site promotion visitor tracking implementing e-commerce systems linking with sales sites This handy guide also tackles the various elements of page design. It explains how to control a reader's eye flow, how to choose a template system, how to set up a color scheme, and more. Typical of O'Reilly's "Cookbook" series, the Web Site Cookbook is written in a straightforward format, featuring recipes that contain problem statements and solutions. A detailed explanation then follows each recipe to show you how and why the solution works. This question-solution-discussion format is a proven teaching method, as any fan of the "Cookbook" series can attest to. Regardless of your strong suit or your role in the creation and life of a website, you can benefit from the teachings found in the Web Site Cookbook. It's a must-have tool for advancing your skills and making better sites.